Discursive worlds of the language learner: a narrative analysis - Coffey, Simon (Revista Complutense de Educación, 2007)
The analysis of autobiographical narratives has recently been cited as extending our understanding of many key constructs in second language acquisition (SLA) theory. Such approaches take language learning beyond the acquisition/assimilation of linguistic structures to focus on learners as social selves actively enacting a range of social identities through engagement with the “language learning project”. In this article I discuss the theoretical framing for my PhD research for which I analysed the written and spoken language learning (his)stories of six British language “learners” aged between 30 and 62. In telling their stories, learners have recourse to a number of discursive worlds which structure their agency both as language learners and as story-tellers. The interpretive approach used in this study may help us to understand not only how a learner may move diachronically through different identity positions but how these positions are discursively structured.